Pelatihan Pemanfaatan Yellow Trap Sebagai Perangkap Serangga Ngengat di Lahan Bawang Merah Dusun Tegalrejo, Desa Sabrang, Kecamatan Ambulu, Kabupaten Jember - Gallyndra Fatkhu Dinata; Muhammad Zayin Sukri; Tri Rini Kusparwanti; Rindha Rentina Darah Pertami; Refa Firgiyanto; Edi Siswadi; Hanif Fatur Rohman; Fadil Rohman; Eliyatiningsih Eliyatiningsih; Didiek Hermanuadi (Journal of Community Development, 2024)
Tegalrejo Hamlet is in Sabrang Village, one of the villages in Ambulu District, Jember Regency, East Java, where the majority of the population work as farmers. There are farmer groups that help farmers in the process of cultivating shallot fields. Currently, the existing farmer groups are still active, aged 45-65 years. There are many problems experienced in shallot fields, namely attacks by onion caterpillar pests which are caused by moth larvae. The solution given is the use of yellow traps. Yellow trap control is an alternative control solution that is environmentally friendly and increases efficiency in processing and production results from farmers. The method used is counseling and demonstration. This extension will be carried out in May 2024. The results of this activity show that farmers are open and accept the solutions we provide well and apply the solutions we provide to their respective shallot fields. From this outreach activity, it is hoped that farmers and Tegalrejo Village farmer groups will become pioneers in using yellow traps in shallot fields to suppress moth attacks.